MON-486 Polygenic Susceptibility to Papillary Thyroid Cancer in Italian Subjects - Brigante, Giulia (J Endocr Soc, 2020)
INTRODUCTION AND AIM. Thyroid cancer is the most common endocrine neoplasia, with an estimated age-standardized incidence rate of 6.7 per 100000 worldwide in 2018 [1]. This rate is rapidly increasing and papillary thyroid carcinoma (PTC) is the main histotype. PTC susceptibility is the result of genetic predisposition, environmental factors and lifestyle. We studied the genetic combination that characterizes PTC affected subjects, differentiating them from healthy controls. METHODS AND RESULTS. We considered the genetic variants (SNPs) significantly associated with PTC on the PubMed database. 184 informative SNPs were selected, considering linkage disequilibrium. Then, SNPs data were extracted from the online 1000 Genomes database, comprising genome of 2504 unselected individuals collected worldwide. The combination of 184 SNPs associated with PTC was used to group individuals in different risk-clusters according to their genetic structure, calculated by Bayesian statistics, as previously performed for polycystic ovary syndrome [2]. Individuals were distributed among 7 groups worldwide, indicating different degree of genetic predisposition to PTC. We then considered genetic data from about 1200 individuals (697 PTC versus 497 healthy controls) of Central/South Italian origin registered in a GWAS, specific for PTC [3]. This first analysis was refined using the 33 SNPs reasonably most causative of genetic clustering (26 with p<0.05 at trend test in GWAS and 7 with p<0.05 in the model of recessive inheritance). At multivariate logistic regression analysis, PTC and healthy controls resulted genetically different (ODDS RATIO 188.6, 95%CI 64.35-552.8), revealing diverse predisposition to develop cancer. Afterwards, these results have been confirmed in an independent cohort of Italian subjects (234 PTC and 100 controls). Then, the genetic structure of each subject was indicated as a percentage of affinity to each risk-cluster and re-analyzed together with other risk factors: sex, body-mass index, area of origin and familiarity (quantified in a growing score as the degree of kinship increases). These data were analyzed together by principal component analysis and clustering of the two groups was even more pronounced. The most contributive factors to the diversity between PTC and healthy controls were genetics and familiarity. CONCLUSION. We demonstrated that PTC affected subjects are genetically different from healthy controls, and that the difference is identifiable in a peculiar combination of genetic variants. REFERENCES 1. Bray F et al. CA: a cancer journal for clinicians. 2018; 68 (6):394-424 2. Casarini and Brigante. JCEM. 2014; 99:E2412-20 3. Köhler et al. Genome-wide association study on differentiated thyroid cancer. J Clin Endocrinol Metab. 2013;98:E1674-81.